AKTIVITAS DARI INDUSTRI RUMAH PANGGUNG DI DESA TOMBASIAN ATAS KECAMATAN KAWANGKOAN BARAT - Claudio Biorhof Ering; Caroline Betsi Diana Pakasi; Ellen Grace Tangkere (Sam Ratulangi University, 2019)
The purpose of this research is to analyze the activities of the stilt house industry. The sampling method in this study uses a purposive sampling method with a total sample of 15 respondents from a population of 36 owners of stilt house industries in the Upper Tombasian Village. The research results show that the activities of the stage house industry in the Upper Tombasian Village include production activities, namely the preparation of raw materials, the design process, ordering, and distribution. Production activities from the stilt house industry provide income where labor is absorbed from within the village itself, depend on number of rooms each house. Thet are 1 room (6 x 5) absorbs 3 workers, 2 rooms (7 x 9) absorb 4 workers, 3 rooms (7 x 12) absorb 5 workers. Income for owners where the owner owns a stilt house business, income for the village through tax collection for every 1 unit of house sold. Income for the surrounding community in the form of renting a vehicle for the distribution process is Rp. 600,000 - Rp. 1,200,000, depending on distance traveled.*eprm*